2010
DOI: 10.1007/s11430-010-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of native aluminum and its possible origin from prospective gas hydrate areas in the South China Sea

Abstract: Aluminum is an active amphoteric metal element, but native aluminum (Al°) can be formed and preserved in special conditions so that its occurrence has unique geological significance. In this paper, the coarse fractions (> 63 μm) of 269 samples of surface sediments and of 165 sediment samples in four cores from the South China Sea (SCS) were picked out and analyzed. Al° particles were found in only five surface samples and three samples in two sedimentary cores. The particles are grayish or silver white in colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…The trough areas such as Zengmu, Wan' an, Nanwei, Nansha and Beikang in southern SCS are reported to store rich hydrocarbon gas and gas hydrate resources, and southern SCS has tectonic environment conducive to the migration of hydrocarbon-rich fluids and extensive methane outlets (Zhu et al, 2001;Wang et al, 2006;Yao, 2007;Zhang et al, 2010;Liu et al, 2011;Trung, 2012;Wei et al, 2012). In the Beikang Basin, some evidences that may indicate existence of cold seeps have been found, including some geophysical features (such as BSR) and authigenic minerals (such as authigenic pyrite) (Figure 1) (Wang et al, 2003;Su et al, 2005;Chen et al, 2009;Chen Z. et al, 2010;Liu et al, 2011). Nonetheless, till now there are only two studies focusing on the activities of cold seeps in the Beikang Basin (Yao, 2007;Li et al, 2018;, their studies showed that the sulfatemethane transition zones (SMTZ) of the four sites are between 5.3 and 8.8 mbsf and the dissolved SO 2− 4 was predominantly consumed by the anaerobic oxidation of methane (AOM) at rates between 27 and 44 mmol m −2 yr −1 only by geochemical characteristics and model of porewater near our study area in the Beikang Basin .…”
Section: Introductionmentioning
confidence: 99%
“…The trough areas such as Zengmu, Wan' an, Nanwei, Nansha and Beikang in southern SCS are reported to store rich hydrocarbon gas and gas hydrate resources, and southern SCS has tectonic environment conducive to the migration of hydrocarbon-rich fluids and extensive methane outlets (Zhu et al, 2001;Wang et al, 2006;Yao, 2007;Zhang et al, 2010;Liu et al, 2011;Trung, 2012;Wei et al, 2012). In the Beikang Basin, some evidences that may indicate existence of cold seeps have been found, including some geophysical features (such as BSR) and authigenic minerals (such as authigenic pyrite) (Figure 1) (Wang et al, 2003;Su et al, 2005;Chen et al, 2009;Chen Z. et al, 2010;Liu et al, 2011). Nonetheless, till now there are only two studies focusing on the activities of cold seeps in the Beikang Basin (Yao, 2007;Li et al, 2018;, their studies showed that the sulfatemethane transition zones (SMTZ) of the four sites are between 5.3 and 8.8 mbsf and the dissolved SO 2− 4 was predominantly consumed by the anaerobic oxidation of methane (AOM) at rates between 27 and 44 mmol m −2 yr −1 only by geochemical characteristics and model of porewater near our study area in the Beikang Basin .…”
Section: Introductionmentioning
confidence: 99%